Soil Salinity: Effect on Vegetable Crop Growth. Management Practices to Prevent and Mitigate Soil Salinization - Machado, Rui; Serralheiro, Ricardo (Horticulturae, 2017)
Salinity is a major problem affecting crop production all over the world: 20% of cultivated land in the world, and 33% of irrigated land, are salt-affected and degraded. This process can be accentuated by climate change, excessive use of groundwater (mainly if close to the sea), increasing use of low-quality water in irrigation, and massive introduction of irrigation associated with intensive farming. Excessive soil salinity reduces the productivity of many agricultural crops, including most vegetables, which are particularly sensitive throughout the ontogeny of the plant. The salinity threshold (ECt) of the majority of vegetable crops is low (ranging from 1 to 2.5 dS m−1 in saturated soil extracts) and vegetable salt tolerance decreases when saline water is used for irrigation. The objective of this review is to discuss the effects of salinity on vegetable growth and how management practices (irrigation, drainage, and fertilization) can prevent soil and water salinization and mitigate the adverse effects of salinity.